Pengaruh Pernikahan Dini terhadap Penanaman Akidah Keluarga di Desa Bandar Selamat Kecamatan Aek Kuo Labuhanbatu Utara - Harahap, Akbar Zailani; Zulkarnaen, Zulkarnaen; Harahap, Salahuddin (Lembaga Yasin AlSys, 2024)
This research aims to determine the influence on religious beliefs in family, where before getting married you must prepare knowledge in religious beliefs. Therefore, there is a belief that is instilled in the family from an early age because this is very important in family life if it has been built from an early age in the parents' family. The method used in this research is qualitative research (field research), data collected through observation, interviews, documentation. This method is used by researchers in their collection activities so that these activities become systematic and made easier by them. Researchers' findings in this study For them, marriage does not depend on age, whether they are young or old, if they have found a suitable partner then getting married is normal and natural. The lack of family beliefs influences children's parenting patterns, parents' strategies for instilling religious values in early childhood in Bandar Selamat Village. Several efforts are made by parents to provide encouragement to children such as giving advice, giving encouragement, giving praise and providing motivation. Meanwhile, in their role as role models, parents make various efforts by providing examples to their children, such as taking children to the mosque to pray in congregation, getting children used to reciting the Koran at tpq or at home. Meanwhile, the role of parents as supervisors is carried out by parents by observing children's daily behavior, monitoring children when playing with friends and accompanying children when they are outside the home.